Huangqi Fuzheng decoction exerts antitumor activity by inhibiting cell growth and inducing cell death in osteosarcoma - Jinghao Qin (Biomedicine & Pharmacotherapy, 2019)
Huangqi Fuzheng decoction (HFD) is a traditional Chinese medicine and has been used as adjuvant clinical therapy for breast, ovarian and thyroid cancer. However, the potential roles and molecular mechanisms of HFD in osteosarcoma remain unclear. Here, we investigated the antitumor activity of HFD in osteosarcoma and analyzed its active compounds and therapeutic targets using an integrated systems pharmacology approach. We found that HFD treatment obviously suppressed cell proliferation and induced cell death of U2OS and Saos-2 cells. In addition, HFD treatment significantly inhibited tumor growth and in combination with Cisplatin treatment without obvious serious side effects in the osteosarcoma xenograft mice. Based on systems pharmacology analysis, we identified 105 active compounds and 23 potential targets for HFD in osteosarcoma. Finally, multi-targets were validated as therapeutic targets of HFD for osteosarcoma using Western blot. Our study provides a liable strategy to explore the molecular mechanisms of traditional Chinese medicine. These findings also suggest HFD as a promising candidate medicine for osteosarcoma treatment.